Пути взаимодействия библиотеки, радио и телевидения в активизации чтения юношества - Лепик, Айра (Knygotyra, 1987)
The tasks of librarians in the raising of the cultural level of reading can find an optimum solution only by a complex approaching to the book propaganda connecting into a unified system all institutions directly involved in the guidance of teenagers – readers: schools, Komsomol organizations, mass media, family. companions of the same age, circles and clubs of hobbies. The object of our research was the problem of potential collaboration possibilities of libraries, radio and television and of their use in the raising of young people’s cultural level of reading. Subject of investigation – reading demands and interests of teenagers, the contents of their reading, their disposition and actual appeal to radio and television. The present paper motivates and explains the essence of the possible influence (indirect and direct) of broad- and telecasts and its connection with the reading regulation. A continual information on books and articles comlementing broad and telecasts, the librarian’s skill to sec radio and television in close connection with library work and to make use of wide influence of radio and television on young people and of their interest in mass media guarantee a successful effect on the raising of young people’s cultural level of reading.